1979
DOI: 10.1159/000122867
|View full text |Cite
|
Sign up to set email alerts
|

Induced Ovulation in Aged Female Rats by L-dopa Implants into the Medial Preoptic Area

Abstract: Direct placement of L-dopa into the medial preoptic area (MPOA) of aged pseudopregnant or constant vaginal estrous female rats resulted in a reinitiation of vaginal cycles and ovulation. Similar treatment with L-dopa in the dorsomedial septum or cortex was ineffective. Direct placement of leucine into any of the three brain regions did not have an effect on ovarian function. Intermittent treatment with L-dopa to MPOA was found to reinstate and maintain vaginal cycles in constant estrous females only when admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1983
1983
1989
1989

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Because the medio basal hypothalamus (MBH) and the medial preoptic area (MPOA), with their widely recognized role in neuroendo crine interactions, have a dense monoaminergic innervation, attention has been preferentially paid to these areas. Thus, Received: August 16, 1983 Accepted after revision: January 9, 1984 changes in the secretion of gonadotropins have been found after manipulating CA and 5-HT in those regions by differ ent means such as lesioning their afferent monoaminergic fibers [9, 21,24, 29, 30, 33,36,44] or local administration of monoamine agonists [12, 28], neurotoxins [6, 21, 29,41,44], and antimetabolites [46], Systemic treatments with the latte' substances can also prevent the effects of the electrical stimulation of these areas on gonadotropin secretion [18,27].However, most of the above-cited studies were conduct ed on female rats, and the information on such phenomena in the male is very limited [29,36,44], Furthermore, there arc other brain areas, especially some limbic structures, which share with the hypothalamus both properties of influencing reproductive function and receiving a significant fraction of the CA and 5-HT fibers which, arising from the brain stem, ascend through the medial forebrain bundle (MFB) [19].The present study was planned to investigate the relativecontribution of 5-HT and CA innervation of MBH, MPOA amygdala (AMY), and other structures connected by the MFB to the control of male gonadal function. Brain M onoam ines and G onadotropins 157 In a first approach, the effects on serum and pituitary levels of gonadotropins and serum androgens of injecting in those areas the monoamine neurotoxins 5,7-dihydroxytryptaniine (5,7-DHT) and 6-hydroxydopamine (6-OHDA) were compared.…”
mentioning
confidence: 99%
“…Because the medio basal hypothalamus (MBH) and the medial preoptic area (MPOA), with their widely recognized role in neuroendo crine interactions, have a dense monoaminergic innervation, attention has been preferentially paid to these areas. Thus, Received: August 16, 1983 Accepted after revision: January 9, 1984 changes in the secretion of gonadotropins have been found after manipulating CA and 5-HT in those regions by differ ent means such as lesioning their afferent monoaminergic fibers [9, 21,24, 29, 30, 33,36,44] or local administration of monoamine agonists [12, 28], neurotoxins [6, 21, 29,41,44], and antimetabolites [46], Systemic treatments with the latte' substances can also prevent the effects of the electrical stimulation of these areas on gonadotropin secretion [18,27].However, most of the above-cited studies were conduct ed on female rats, and the information on such phenomena in the male is very limited [29,36,44], Furthermore, there arc other brain areas, especially some limbic structures, which share with the hypothalamus both properties of influencing reproductive function and receiving a significant fraction of the CA and 5-HT fibers which, arising from the brain stem, ascend through the medial forebrain bundle (MFB) [19].The present study was planned to investigate the relativecontribution of 5-HT and CA innervation of MBH, MPOA amygdala (AMY), and other structures connected by the MFB to the control of male gonadal function. Brain M onoam ines and G onadotropins 157 In a first approach, the effects on serum and pituitary levels of gonadotropins and serum androgens of injecting in those areas the monoamine neurotoxins 5,7-dihydroxytryptaniine (5,7-DHT) and 6-hydroxydopamine (6-OHDA) were compared.…”
mentioning
confidence: 99%
“…On the other hand. Cooper et al [6] reported that ovu latory cycles could be induced in old constant-estrous rats which presumedly exhibit low sensitivity of the negative es trogen feedback [3,28] and reduced hypothalamic DA con tent and turnover [33], by the intermittent medial preoptic implantation of L-dopa during vaginal estrus and metest rus, but not if the implants were in place from diestrus to proestrus or from proestrus to estrus. The results suggest that diminution of the medial preoptic DA activity, which was prevented by the implantation of apomorphine, may be required for normal preovulatory follicular development.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with precursors to CNS CAs, such as L‐tyrosine and L‐dopa, 64–67 and monoamine oxidase inhibitors such as iproniazid 64 will restore vaginal cycles and ovulation in old CE females. Furthermore, direct placement of L‐dopa into the medial preoptic area (MPOA) will also reinstate vaginal cycling and ovulation 68 . Clemens et al 69 also have shown that ovulation could be induced in the aged CE female by electric stimulation of the MPOA.…”
Section: Reproductive Senescence In the Female Ratmentioning
confidence: 99%